Multiobjective Scheduling of Hybrid Synchronization Messages - Parizotto, Ricardo; Mello, Braulio (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2022: Anais do XLIX Seminário Integrado de Software e Hardware, 2022)
One of the essential aspects of distributed simulations is to order events according to a causal consistency model. However, traditional approaches are costly in terms of processing to ensure causality. A promising approach to order events is using a hybrid synchronization approach, where processes can alter dynamically between optimistic and conservative approaches. Unfortunately, synchronizing processes running a hybrid synchronization is a complex problem. In this work, we discuss a multi-objective scheduling of hybrid synchronization messages problem. Beyond that, we propose using a scheduling algorithm and describe how to integrate the algorithm in an existing distributed simulator. Finally, we propose a preliminary analysis of our algorithm regarding work done and the number of messages.